Corporatisation of higher institutions in Malaysia:Complacency Or Misinterpretation. - Kassim, Zakaria (1996)
The Malaysian Government, led by the National Front pofitieal Parties since independence in 1957,had taken steps to develop the country through various short and long term policies. Malaysia is recognized as a "new industrialized country in the region".